Pinocchio - Collodi, Carlo, 1826-1890.; Fiammenghi, Gioia (Baltimore : Penguin Books, 1974)
The adventures of a talking wooden puppet whose nose grew longer whenever he told a lie.
Translation of Le avventure di Pinocchio.
Keywords: Fantasy; Puppets -- Fiction